AB0293 Frequency of joint erosions in patients with rheumatoid arthritis, treated with biologics in relation to rf and acpa serology in real life. (12th June 2018) - Heeman, L.; Van den Bosch, F.; Elewaut, D.; Carron, P.; Jacques, P.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic auto-immune disease, characterised by a symmetric polysynovitis and extra-articular manifestations. In 70% to 80% of patients with RA, serologic factors like Rheumatoid Factor (RF) and Anti-Citrullinated Protein Antibodies (ACPA) are present. Early recognition and treatment with disease-modifying antirheumatic drugs (DMARDs) is important in achieving control of disease and prevention of joint destruction. If it is untreated or unresponsive to therapy, inflammation destroys cartilage and bone, resulting in irreversible bone erosions. The 2016 EULAR recommendations for the management of RA stipulate that MTX is recommended as first-line strategy plus short-term GC, aiming at >50% improvement within 3 and target attainment within 6 months. If this fails, stratification is recommended. Without unfavourable prognostic markers, switching to, or adding another csDMARDs (plus short-term GC) is suggested. In the presence of unfavourable prognostic markers (autoantibodies, high disease activity, early erosions, failure of 2 csDMARDs), any bDMARD or Jak-inhibitor should be added to the csDMARD. Objectives: To determine an association between serology status and prevalence of radiographic erosions, the use of biologics and prevalence of erosions, and serology status and use of biologics. Methods: Data were obtained from the electronic patient files of patients who visited the department of Rheumatology at the University Hospital of Ghent (Belgium) between October and December 2016. Patient characteristics with respect to diagnosis, treatment, serology status and erosion status were collected. The data has been statistically analysed using χ 2 ;-, Fisher's exact, Kolmogorov-Smirnov en Kruskal-Wallis tests with α=0, 05. Results: A total of 2001 consultations were analysed, of which 358 patients were identified with RA. 353 patients were included, of which 116 men (32, 9%) and 237 women (67, 1%). The mean age of the study population was 62 years with a mean age of 52 years at diagnosis. Of these patients, 36, 0%, 49, 5% and 29, 8% were positive for respectively RF, ACPA and RF +ACPA. 38% has ever been treated with a biologic, whereas 26, 9% is currently treated with a biologic. 37, 4% of the patients showed erosions on a recent radiograph of hands or feet. A positive ACPA serology (p<0, 0001. OR=1, 87), a positive RF serology (p=0010. OR=2, 26) and a positive RF +ACPA serology (p=0007. OR=2, 74) was more observed in patients with radiographic erosions. A significant difference in erosions was seen between patients treated with or without biologicals (p<0, 0001. OR=3, 45). Biologicals were prescribed more in patients with positive ACPA serology (p<0, 0001. OR=3, 92) and in patients with positive RF serology (p=0001. OR=2, 67). Conclusions: In a consecutive real life cohort of patients with RA, positive ACPA and/or RF status were associated with an increased risk to develop bone erosions in affected joints. Positive serology was also linked to biologic therapies. Patients who received biological treatment were more prone to have erosions. Disclosure of Interest: None declared